2011
DOI: 10.1121/1.3514518
|View full text |Cite
|
Sign up to set email alerts
|

Manipulations of listeners’ echo perception are reflected in event-related potentials

Abstract: To gain information from complex auditory scenes, it is necessary to determine which of the many loudness, pitch, and timbre changes originate from a single source. Grouping sound into sources based on spatial information is complicated by reverberant energy bouncing off multiple surfaces and reaching the ears from directions other than the source's location. The ability to localize sounds despite these echoes has been explored with the precedence effect: Identical sounds presented from two locations with a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 47 publications
(77 reference statements)
5
21
1
Order By: Relevance
“…First, the data suggest that buildup is reduced or "depressed" following a leadalone conditioner compared to an equivalent period of silence; this agrees well with previous observations (Sanders et al, 2011). Second, the data suggest that buildup is enhanced following a lag-alone conditioner compared to an equivalent period of silence.…”
Section: Methodssupporting
confidence: 81%
See 4 more Smart Citations
“…First, the data suggest that buildup is reduced or "depressed" following a leadalone conditioner compared to an equivalent period of silence; this agrees well with previous observations (Sanders et al, 2011). Second, the data suggest that buildup is enhanced following a lag-alone conditioner compared to an equivalent period of silence.…”
Section: Methodssupporting
confidence: 81%
“…Our findings join and complement a growing corpus of reports exploring the effects of lead-alone click trains on echo suppression (Freyman et al, 1991;Keen and Freyman, 2009;Sanders et al, 2011). First, data reported by Freyman et al (1991) demonstrated that echo thresholds of isolated lead-lag pairs decreased following a lead-alone conditioner, albeit in the absence of any explicit attempt to elicit buildup.…”
Section: A Effects Of Unpaired Click Trains On Buildupsupporting
confidence: 62%
See 3 more Smart Citations